Thinking about thinking what educators need to know - Ee, Jessie (McGraw Hill, 2004)
The new millennium calls for a breakthrough in the way we learn and think. How can we enhance the flexibility of the mind so that the spirit of innovation and enterprise can flourish and flow in those we nurture and teach? What do we know about the important roles played by attitudes, dispositions, intellectual habits, and motivation in the development of thinking? This book captures the latest research and applications in these fields with contributions by some of the most renowned researchers and practitioners intimately involved in research and pedagogy in self-regulated learning and metacognition. Part 1 provides the Theory and Research which includes: key features of the classroom that can facilitate the learning of self-regulated learning strategies; how teachers can be effective as reflective practitioners; research on the relationship between teachers' classroom practices and the different ability groups that they teach; and research on cross-cultural practices of teachers.Part 2 emphasizes the Practice and Applications pertaining to Self-regulated Learning and Metacognition which includes: problem-based learning approaches in enhancing self-directed learning and metacognition; need for teachers to scaffold learning application of self-regulation in reading, science, and mathematics problem-solving; how assessment, teachers, and instruction interact in helping students to be self-regulated and strategic learners; strategies for helping attention deficit hyperactivity disorder (ADHD) adolescents in self-regulation. Educators and academics will find this comprehensive book an invaluable contribution to advancing the knowledge and practice of teaching thinking.